Delineation of seed collection zones based on environmental and genetic characteristics for Quercus suber L. in Sardinia, Italy - De Dato, G; Teani, A; Mattioni, C; Marchi, M; Monteverdi, MC; Ducci, F (IForest (Viterbo), 2018)
The assessment of seed zones or regions of provenance (RoP) to preserve local adaptation of tree species is an effective tool for the correct management of forest reproductive materials. The RoP for a species or sub-species is the area or group of areas subject to sufficiently uniform ecological conditions in which stands or seed sources show similar phenotypic or genetic characters, taking into account altitudinal boundaries where appropriate. However, the delineation of RoPs is commonly based on estimates of intrinsic environmental homogeneity, mainly climate and/or soil characteristics. The integration of genetic data into RoP maps is an important strategy to obtain a sound tool for managing forest reproductive materials. A study on Quercus suber (cork oak) in Sardinia (Italy) was carried out with the aim of determining ecological regions of provenance, investigating the genetic diversity among populations at the regional scale and identifying possible areas of interest for valorising the available germplasm. Identification of these areas was performed by Reserve Selection Analysis, which allows to identify priority areas by assessing the minimum number of sites required to include all the genetic diversity estimated by genetic analysis. Four spatial clusters were obtained based on environmental data: the northern and northern-eastern parts of the island were included in the Northern RoP; the second RoP covered the western part; and the third RoP enclosed the south-eastern region. The last group was distributed on the central part of the island (Central RoP) and includes the higher elevations. The sampled populations showed a low differentiation among populations and low diversity. According to the Reserve Selection Analysis, four conservation priority areas were identified. These indications can be useful at the local level because these sites can be proposed as stands for seed collection for future plantations.